(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2023)
Business intelligence applications are in the front of demanding technologies. Companies need technology to adapt to changing requirements, to deal with a rich amount of data, to get correct information, to analyze data, and finally to quickly support decision-makers. Developing a Business Intelligence (BI) application can be defined as a short-delivering software application. This process is based on frequently adapting to changing requirements, involving customer participation, and delivering high-quality applications. Agile teams need a set of reliable metrics to measure their performance at different three levels: functionality, content, and scalability. This paper proposes Goal Question Agility Metrics (GQAM) that can be used in measuring the performance of agile teams working in developing business intelligence applications. GQAM is based on the Goal Question Metrics (GQM) method that was developed by Victor Basili in 1994 [19]. In addition, GQAM depends on agile and BI concepts. GQAM proposes a set of metrics that are used to measure performance. The GQAM will be subjected to experiments using a real data set in the future.